2016
DOI: 10.1002/ptr.5675
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicines in Idiopathic Heavy Menstrual Bleeding: A Systematic Review

Abstract: Idiopathic heavy menstrual bleeding (HMB; IHMB) is a common gynecological problem with no pelvic pathology or general bleeding disorder. Herbal remedies are commonly used to treat HMB. This systematic review aimed to assess the effectiveness and safety of herbal preparations for the treatment of IHMB. MEDLINE, Ovid, and the Cochrane Central Register of Controlled Trials were searched from inception to 23 August 2015. Only randomized controlled trials were considered. Three randomized controlled trials were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Although few studies have been conducted on the use of medicinal plants to reduce menstrual bleeding (18,19), there was only one study on the effectiveness of dry cupping as before and after the intervention, with a limited sample size (n = 15) in India. In that study, a significant difference was found between the severity of the bleeding before and after the intervention (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies have been conducted on the use of medicinal plants to reduce menstrual bleeding (18,19), there was only one study on the effectiveness of dry cupping as before and after the intervention, with a limited sample size (n = 15) in India. In that study, a significant difference was found between the severity of the bleeding before and after the intervention (20).…”
Section: Discussionmentioning
confidence: 99%
“…Tannins are considered as astringents 11 and thus can cause the contraction of capillary endothelium and the reduction of uterine bleeding 19 . Flavonoids reduce the synthesis of endometrial prostaglandins and consequently reduce extensive uterine bleeding 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, according to a systematic review, further well-designed trials are recommended to investigate the safety and efficacy of herbs in the treatment of women with menorrhagia (22). To the best of our knowledge, no study has so far assessed the effects of quince on menstrual bleeding.…”
Section: Introductionmentioning
confidence: 99%